Proposed design of the application of chemical warehouse control systems with the water fall method - Rosihin, Rosihin; Septian, Muhammad Hafizh (AGUSPATI Research Institute, 2025)
This study aims to make it easier for analysts to collect chemicals and maintain the accuracy of chemical inventory data because they no longer use manual recording. The research was conducted at the laboratory of PT. Mitsubishi Chemical Indonesia March 1 to May 30, 2024. Data were collected by interview and observation, and analyzed using the water fall method. Based on the research, it can be concluded that: 1) the system created can make it easier for the analyst when taking chemicals and the suitability of the inventory quantity data becomes accurate, 2) the application made can be easily understood by all analysts in the laboratory.